First report of spotted fever group Rickettsia aeschlimannii in Hyalomma turanicum, Haemaphysalis bispinosa, and Haemaphysalis montgomeryi infesting domestic animals: updates on the epidemiology of tick-borne Rickettsia aeschlimannii - Majid, Abdul; Almutairi, Mashal M.; Alouffi, Abdulaziz; Tanaka, Tetsuya; Yen, Tsai-Ying; Tsai, Kun-Hsien; Ali, Abid (Frontiers in Microbiology, 2023)
Tick-borne Rickettsia spp. have long been known as causative agents for zoonotic diseases. We have previously characterized Rickettsia spp. in different ticks infesting a broad range of hosts in Pakistan; however, knowledge regarding Rickettsia aeschlimannii in Haemaphysalis and Hyalomma ticks is missing. This study aimed to obtain a better understanding about R. aeschlimannii in Pakistan and update the knowledge about its worldwide epidemiology. Among 369 examined domestic animals, 247 (66%) were infested by 872 ticks. Collected ticks were morphologically delineated into three genera, namely, Rhipicephalus, Hyalomma, and Haemaphysalis. Adult females were the most prevalent (number ₌ 376, 43.1%), followed by nymphs (303, 34.74%) and males (193, 22.13%). Overall, genomic DNA samples of 223 tick were isolated and screened for Rickettsia spp. by the amplification of rickettsial gltA, ompA, and ompB partial genes using conventional PCR. Rickettsial DNA was detected in 8 of 223 (3.58%) ticks including nymphs (5 of 122, 4.0%) and adult females (3 of 86, 3.48%). The rickettsial gltA, ompA, and ompB sequences were detected in Hyalomma turanicum (2 nymphs and 1 adult female), Haemaphysalis bispinosa (1 nymph and 1 adult female), and Haemaphysalis montgomeryi (2 nymphs and 1 adult female). These rickettsial sequences showed 99.71–100% identity with R. aeschlimannii and phylogenetically clustered with the same species. None of the tested Rhipicephalus microplus, Hyalomma isaaci, Hyalomma scupense, Rhipicephalus turanicus, Hyalomma anatolicum, Rhipicephalus haemaphysaloides, Rhipicephalus sanguineus, Haemaphysalis cornupunctata, and Haemaphysalis sulcata ticks were found positive for rickettsial DNA. Comprehensive surveillance studies should be adopted to update the knowledge regarding tick-borne zoonotic Rickettsia species, evaluate their risks to humans and livestock, and investigate the unexamined cases of illness after tick bite among livestock holders in the country.